EFEKTIVITAS MENGUNYAH TEBU (SACCHARUM OFFICINARUM) TERHADAP PENURUNAN INDEKS DEBRIS PADA LEMBAGA PEMBINAAN KHUSUS ANAK KELAS II DI LOMBOK TENGAH TAHUN 2024 - Urwa Nelani Gilda; Jumiati (LPPM STIKES Mataram, 2024)
Introduction: Debris is soft foreign material that remains and sticks to the surface of the teeth. Debris is formed due to poor cleaning of the oral cavity. Sugarcane has the mechanical properties of fiber which can help create a brush-like effect that can clean the surface of the teeth. Objective: To determine the effectiveness of chewing sugar cane (Saccharum officinarum) in reducing the debris index at the Class II Children's Special Development Institute in Central Lombok. Method: Quasy Experimental Research with a a pre-test and post-test design. The total sample was 30 people with purposive sampling technique. Result: Debris index before chewing sugar cane is in poor criteria (53.3%) after chewing sugar cane has decreased to good criteria (50.0%). Data analysis using the T test with the help of SPSS 25 obtained a significance value of 0.000 <0.00. The calculated t value> from the t table value (17.696> 2.045). Conclusion: Sugarcane (Saccharum officinarum) chewing is effective in reducing the debris index at the Central Lombok Class II Special Development Institute.